Use of the rheumatic drug tocilizumab for treatment of SARS-CoV-2 patients - Bogna Grygiel-Górniak (Termedia Publishing House, 2021)
Coronavirus disease 2019 (COVID-19) is a highly infectious respiratory disease caused by a new coronavirus known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which has been observed to vary in its degree of symptoms. One of the most important clinical manifestations is pneumonia and the subsequent worsening of the hyperinflammatory state and cytokine storm. Tocilizumab (TCB) is a recombinant humanized, anti-human monoclonal antibody of the immunoglobulin G1k (IgG1k) subclass that acts against soluble and membrane-bound interleukin six receptors (IL-6R). There is wide use of TCB in rheumatic diseases. However, recently this medication has been used in the treatment of SARS-CoV-2 infection. Tocilizumab application in COVID-19 patients with a high risk of a cytokine storm shows a positive response in reducing the mortality rate. Moreover, TCB minimizes the time needed to recover, improves oxygenation, shortens the duration of vasopressor support, and reduces the likelihood of invasive mechanical ventilation. Therefore we provide an overview of recent studies to understand the efficacy of this drug under various circumstances, including COVID-19 and rheumatic pathologies. This article also explores and integrates the different treatment possibilities in prominent anti-inflammatory and immune-modulatory-related symptoms. The preliminary data demonstrate promising results regarding the efficacy of TCB use in severe COVID-19 patients. Nevertheless, randomized controlled trials, with adequate sample sizes and sufficient follow-up periods, are needed to form conclusions and establish treatment recommendations.